Vowel Inherent Spectral Change - Morrison, Geoffrey Stewart; Assmann, Peter F.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
It has been traditional in phonetic research to characterize monophthongs using a set of static formant frequencies, i.e., formant frequencies taken from a single time-point in the vowel or averaged over the time-course of the vowel. However, over the last twenty years a growing body of research has demonstrated that, at least for a number of dialects of North American English, vowels which are traditionally described as monophthongs often have substantial spectral change. Vowel Inherent Spectral Change has been observed in speakers$1 (Bproductions, and has also been found to have a substantial effect on listeners$1 (Bperception. In terms of acoustics, the traditional categorical distinction between monophthongs and diphthongs can be replaced by a gradient description of dynamic spectral patterns. This book includes chapters addressing various aspects of vowel inherent spectral change (VISC), including theoretical and experimental studies of the perceptually relevant aspects of VISC, the relationship between articulation (vocal-tract trajectories) and VISC, historical changes related to VISC, cross-dialect, cross-language, and cross-age-group comparisons of VISC, the effects of VISC on second-language speech learning, and the use of VISC in forensic voice comparison.s
PERCEPTION AND MODELS: Static and dynamic approaches to understanding vowel perception -- Theories of the perception of vowel inherent spectral change: A review -- Formant trajectories as acoustic correlates to speech perception -- Perception of vowel sounds with a biologically realistic information theoretic model of speech perception -- Dynamic specification theory across languages: An alternative view of vowel spectral change -- DIACHRONY AND SYNCHRONY: The contribution of dynamic formant differences in vowels to diachronic sound change -- Cross-dialectal differences in dynamic formant patterns in American English -- ACQUISITION AND APPLICATION: Developmental patterns in children$1 (Bs speech: Time-varying spectral change in vowels -- Vowel inherent spectral change and the second-language learner -- Vowel inherent spectral change in forensic voice comparison.s
Keywords: Engineering; Translators (Computer programs).; Biometrics; Phonology; Acoustics; Engineering; Signal, Image and Speech Processing; Phonology; Acoustics; Biometrics; Language Translation and Linguistics